Bridging knowledge gaps in fish health management through education, research, and biosecurity - Zornu, Jacob; Tavornpanich, Saraya; Shimaa, Ali E.; Addo, Samuel; Nyaga, Philip; Dverdal, Mona Jansen; Norheim, Kari; Brun, Edgar; Cudjoe, Kofitsyo S. (Frontiers in Sustainable Food Systems, 2023)
Globally, education, research, and biosecurity stand as strong pillars for the sustainable development of aquaculture. To identify the knowledge gaps in education, research, and biosecurity practices related to aquatic animal health management, we conducted a questionnaire-based study in some countries in East and West Africa. Initially, many participants were invited to join the online survey, but ultimately, only 88 individuals participated, primarily from Ghana (47) and Kenya (20), with an additional 21 respondents from five other East and West African countries. The study identified the relevant educational gaps, including the need for additional training in aquatic animal health management, nutrition, and genetics. Respondents emphasized the need for more national aquaculture research institutions and increased funding for these institutions to address industry needs collaboratively. Furthermore the lack of biosecurity measures and a limited understanding of their importance within the industry were prominent concerns among the respondents. Addressing these identified gaps in a holistic manner through the implementation of national policies on aquaculture biosecurity can lead to sustainability within the aquaculture sector. Governments of the represented countries should intervene by providing the necessary logistics and capacity to support aquaculture research and development. Informed government involvement is necessary to bridging the disconnection among all stakeholders, as revealed by the results. This study can serve as a working document to enhance aquatic animal health management in East and West Africa and thus fostering sustainable and resilient aquaculture.